Affordable Care Act–dependent Insurance Coverage and Access to Care Among Young Adult Women With a Recent Live Birth. Issue 2 (February 2019) - Li, Rui; Bauman, Brenda; D'Angelo, Denise V.; Harrison, Leslie L.; Warner, Lee; Barfield, Wanda D.; Cox, Shanna
Abstract : Background: The Affordable Care Act (ACA)-dependent coverage Provision (the Provision), implemented in 2010, extended family insurance coverage to adult children until age 26. Objectives: To examine the impact of the ACA Provision on insurance coverage and care among women with a recent live birth. Research Design, Subjects, and Outcome Measures: We conducted a difference-in-difference analysis to assess the effect of the Provision using data from the Pregnancy Risk Assessment Monitoring System among 22, 599 women aged 19–25 (treatment group) and 22, 361 women aged 27–31 years (control group). Outcomes include insurance coverage in the month before and during pregnancy, and at delivery, and receipt of timely prenatal care, a postpartum check-up, and postpartum contraceptive use. Results: Compared with the control group, the Provision was associated with a 4.7-percentage point decrease in being uninsured and a 5.9-percentage point increase in private insurance coverage in the month before pregnancy, and a 5.4-percentage point increase in private insurance coverage and a 5.9-percentage point decrease in Medicaid coverage during pregnancy, with similar changes in insurance coverage at delivery. Findings demonstrated a 3.6-percentage point increase in receipt of timely prenatal care, and no change in receipt of a postpartum check-up or postpartum contraceptive use. Conclusions: Among women with a recent live birth, the Provision was associated with a decreased likelihood of being uninsured and increased private insurance coverage in the month before pregnancy, a shift from Medicaid to private insurance coverage during pregnancy and at delivery, and an increased likelihood of receiving timely prenatal care. Abstract : Supplemental Digital Content is available in the text.